Induction of Agarwood in Aquilaria malaccensis Using Nitrogen Fertilizer and Fusarium solani) - Resti Wahyuni; Triadiati Triadiati; Syamsul Falah (Jurnal Penelitian Kehutanan Wallacea, 2018)
Aquilaria malaccensis is agarwood producing species in Indonesia. Agarwood compounds are formed as a chemical response of Aquliaria malaccensis tree to various physical damages, phatogen infection, or chemical treatment. Factors influencing agarwood formation are age of the tree, season, geographical location, environment, and treatment period. Agarwood induction may be done in tree or sapling. Agarwood induction in saplings need more effort than in trees. Combination of fungi (Fusarium solani) and nutrient (Nitrogen fertilizer) treatment may be one way to induce agarwood in A. malaccensis saplings. This study aims to produce A. malaccensis agarwood (aromatic compounds and colour) by induction of F. solani and nitrogen fertilizer, and analyse the agarwood chemical content. The agarwood chemical content was investigated by Gas Chromatography Mass Spectrometry (GCMS) analysis. Results indicated that agarwood had a different colour for every treatment. The darkest brown and most fragrant agarwood were produced by A. malaccensis treated by a combination of nitrogen fertilizer (4 gr/sapling) and F. solani inoculation. Three chemical compounds were identified i.e. silanediol dimethyl, 4-ethyl benzoic acid and 1,4,7,10,13,16- hexaoxacyclooctadecane with percentages of 25.7, 17.62, and 3.56 respectively. A. malaccensis treated by nitrogen fertilizer and F. solani for 3 months is able to induce aromatic compounds formation, but the colour still dark brown. Biosynthesis of aromatic compounds in agarwood occurs first before changes in the colour of the wood.